1989
DOI: 10.1002/eji.1830190917
|View full text |Cite
|
Sign up to set email alerts
|

Only dull CD3+ thymocytes bind to thymic epithelial cells. the binding is elicited by both CD2/LFA‐3 and LFA‐1/ICAM‐1 interactions

Abstract: In view of the necessity for thymocytes to interact with thymic epithelial cells to differentiate into mature T cells, this study analyzed the binding between human thymocytes, cultured thymic epithelial cells (CTEC) and the required adhesion molecules. Immediately after separation, thymic epithelial cells (TEC) readily expressed ICAM-1, which is one of the ligands of LFA-1 cell adhesion molecules. However, the ICAM-1 expression was gradually lost upon culture of TEC. IFN-gamma re-induced ICAM-1 on the CTEC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 27 publications
(10 reference statements)
2
17
0
Order By: Relevance
“…Among these, ICAM-1 was shown to be strongly expressed on almost all TNCs, and some TNCs contained cells with either LFA-la or LFA-1B markers, the ligands for ICAM-1. In vitro studies have also revealed that classical cell adhesion molecules (ICAM-1) can mediate intrathymic T cell migration and differentiation (NONOYAMA et al, 1989;SINGER et al, 1990). Although laminin was only faintly expressed in the TNCs, it may also mediate the cell traffic within TNCs, since typical extracellular matrices (fibronectin, laminin) are known to mediate the release of thymocytes from TNCs (SAVINO et al, 1993;VILLA-VERDE et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, ICAM-1 was shown to be strongly expressed on almost all TNCs, and some TNCs contained cells with either LFA-la or LFA-1B markers, the ligands for ICAM-1. In vitro studies have also revealed that classical cell adhesion molecules (ICAM-1) can mediate intrathymic T cell migration and differentiation (NONOYAMA et al, 1989;SINGER et al, 1990). Although laminin was only faintly expressed in the TNCs, it may also mediate the cell traffic within TNCs, since typical extracellular matrices (fibronectin, laminin) are known to mediate the release of thymocytes from TNCs (SAVINO et al, 1993;VILLA-VERDE et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Non-hematopoietic cells such as epithelial cells of the skin [ll],the thymus [12] and the thyroid [13] can be inducedfor ICAM-1 expression by cytokines such as IFN-y, I L l p and TNF-a. In vivo, gut epithelial cells, like keratinocytes, do not constitutively express detectable amounts of ICAM-1 ( [9] and D. Kaiserlian, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Treatment of embryonic thymus in organ culture or in vivo injection of newborn mice with anti-CD2 mAb does not interfere with normal thymocyte differentiation (29,31). (iii) Only TCR/ CD3+ cells have been shown to bind to thymic epithelial cells through a CD2-LFA-3 interaction or to be stimulated as a result of this interaction (32).…”
mentioning
confidence: 99%